Physical and psychological violence at the workplace (Dublin, 2010)
"Workplace violence is a social phenomenon of a certain magnitude. Overall, approximately one in ten European workers report having experienced some form of workplace violence, either physical or psychological, in the previous 12 months. Foundation Findings provide pertinent background information and policy pointers for all actors and interested parties engaged in the current European debate on the future of social policy. The contents are based on Foundation research and reflect its autonomous and tripartite structure."